2002
DOI: 10.1063/1.1506141
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of site-specific reaction of H2 on Cu(100)

Abstract: Six-dimensional quantum dynamical calculations are presented for the reaction of (v, j) H 2 on Cu͑100͒, at normal incidence, for vϭ0 -1 and jϭ0 -5. The dynamical calculations employed a potential energy surface computed with density functional theory, using the generalized gradient approximation and a slab representation for the adsorbate-substrate system. The aim of the calculations was to establish signatures from which experiments could determine the dominant reaction site of H 2 on the surface and the depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 100 publications
4
45
0
Order By: Relevance
“…Impact on the top site has been found to be relevant for vibrationally inelastic scattering and for dissociation of vibrationally excited and highly rotationally excited H 2 on Cu(100). 40,46,57 The 2D elbow for this dissociation route shows a large curvature of the reaction path and an especially late barrier (occurring at a large H-H distance r, see Fig. 3 and Table I).…”
Section: B Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact on the top site has been found to be relevant for vibrationally inelastic scattering and for dissociation of vibrationally excited and highly rotationally excited H 2 on Cu(100). 40,46,57 The 2D elbow for this dissociation route shows a large curvature of the reaction path and an especially late barrier (occurring at a large H-H distance r, see Fig. 3 and Table I).…”
Section: B Computational Methodsmentioning
confidence: 99%
“…45 The system was also used to uncover experimental signatures of site reactivity in work bearing a close relationship to the present work, as the suggested experimental signature involves the relationship between measured rotational quadrupole alignment parameters of H 2 (v = 0, j) and (v = 1, j) just above the reaction threshold. 46, 47 H 2 + Cu(100) was also used as a benchmark to demonstrate a new, symmetry adapted pseudospectral method. 48 Finally, more recently the system has been used to explore the applicability of a mean field quantum dynamics method to investigate the effect of phonons on reactive and non-reactive scattering of H 2 from copper surfaces.…”
mentioning
confidence: 99%
“…Many previous researches showed that the catalytic properties of clusters are structure dependent, leading to different adsorption energies and sites for different structures of clusters [1][2][3][4][5][6]. Hydrogen is employed in many modern technologies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], so surface reactions of hydrogen molecules in transition metals have been carried out over the adsorption and desorption of hydrogen and deuterium molecules on well-defined single crystal metals. Axel Pramann et al [22] studied hydrogen chemisorption rates and electronic structures of small Nb n Al -clusters by photoelectron spectroscopic method.…”
Section: Introductionmentioning
confidence: 99%
“…Such a preference is often seen in activated reactions at low collision energies and arises because the anisotropy of the PES is generally large in the polar angle, leading to enhanced reaction due to rotational deexcitation of rotational states with low ͉m J ͉. 39,52 This is also the likely cause in this case: the ͑J =2, m J =0͒ state can deexcite, freeing some energy to overcome any low barriers encountered. In addition, the ͑J =2, m J =2͒ state is more tilted with respect to the surface plane than helicopter states for higher J. Helicoptering molecules for J = 2 are thus less favorably aligned to react than they are for higher initial rotational states.…”
Section: Alignmentmentioning
confidence: 99%
“…5͑a͔͒. 16,32,[37][38][39] In the HE range, the dissociation is predominantly direct in nature, while in the LE range the direct and indirect components both contribute ͓Fig. 5͑b͔͒.…”
Section: -7mentioning
confidence: 99%